2014
DOI: 10.1371/journal.pone.0105694
|View full text |Cite|
|
Sign up to set email alerts
|

Like or Dislike? Affective Preference Modulates Neural Response to Others' Gains and Losses

Abstract: Previous studies have demonstrated that the brain responds differentially to others' gains and losses relative to one's own, moderated by social context factors such as competition and interpersonal relationships. In the current study, we tested the hypothesis that the neural response to others' outcomes could be modulated by a short-term induced affective preference. We engaged 17 men and 18 women in a social-exchange game, in which two confederates played fairly or unfairly. Both men and women rated the fair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…In comparison to strangers, participants’ empathic responses toward close friends were only salient when they did not directly participate in a gambling game (Leng and Zhou, 2010; Ma et al, 2011; Wang et al, 2014b). Research also suggests that the larger the extent of self-benefit involvement, the more likely it is that egoism will influence one’s affective response toward others’ monetary outcomes (Wang et al, 2014a). Our findings complement those studies; that is, in demonstrating on the contrary that people are not wholly concerned about personal interests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to strangers, participants’ empathic responses toward close friends were only salient when they did not directly participate in a gambling game (Leng and Zhou, 2010; Ma et al, 2011; Wang et al, 2014b). Research also suggests that the larger the extent of self-benefit involvement, the more likely it is that egoism will influence one’s affective response toward others’ monetary outcomes (Wang et al, 2014a). Our findings complement those studies; that is, in demonstrating on the contrary that people are not wholly concerned about personal interests.…”
Section: Discussionmentioning
confidence: 99%
“…We are used to evaluating others’ outcomes from an egocentric perspective. The larger the extent to which self-benefit is involved, the more likely it is that egoism will influence one’s affective response toward others’ monetary outcomes (Wang et al, 2014a). The stronger empathy for a friend compared to a stranger may also be because the friend is self-related, in that the participants may have selfish incentives for increasing the chance of future cooperative interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies also showed a “mirror” performance monitoring system in which observing another’s gain or loss also evokes similar FRN, which is called observational FRN (oFRN), as it applies in observation situations (Kang et al, 2010; Wang Y. et al, 2014). Fukushima and Hiraki (2009) found that significant oFRN was elicited only when humans were in observation, not computer players.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its significant role in social interaction, pain empathy has become an intense area of research in psychology and neuroscience ( Sassenrath et al, 2016 ; Yang et al, 2017 ). Recently, a large body of studies have investigated whether and how pain empathy is affected by social factors such as sense of fairness ( Singer et al, 2006 ), monetary reward ( Guo et al, 2012 ; Goerlich et al, 2016 ), affective preference ( Wang et al, 2014 ; Yang et al, 2014 ), social distance ( Zaki, 2014 ; Wang et al, 2016 ), as well as competition and cooperation ( Cui et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%